Social Networks and the Risk of Gunshot Injury. - Papachristos, Andrew; Braga, Anthony; Hureau, David (Journal of Urban Health, 2012)
Direct and indirect exposure to gun violence have considerable consequences on individual health and well-being. However, no study has considered the effects of one's social network on gunshot injury. This study investigates the relationship between an individual's position in a high-risk social network and the probability of being a victim of a fatal or non-fatal gunshot wound by combining observational data from the police with records of fatal and non-fatal gunshot injuries among 763 individuals in Boston's Cape Verdean community. A logistic regression approach is used to analyze the probability of being the victim of a fatal or non-fatal gunshot wound and whether such injury is related to age, gender, race, prior criminal activity, exposure to street gangs and other gunshot victims, density of one's peer network, and the social distance to other gunshot victims. The findings demonstrate that 85 % all of the gunshot injuries in the sample occur within a single social network. Probability of gunshot victimization is related to one's network distance to other gunshot victims: each network association removed from another gunshot victim reduces the odds of gunshot victimization by 25 % (odds ratio = 0.75; 95 % confidence interval, 0.65 to 0.87). This indirect exposure to gunshot victimization exerts an effect above and beyond the saturation of gunshot victimization in one's peer network, age, prior criminal activity, and other individual and network variables.